2010
DOI: 10.2214/ajr.09.3717
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of CT Signs of Right Ventricular Dysfunction in Acute Pulmonary Embolism

Abstract: Contrast medium-enhanced pulmonary CT angiography (CTA) is increasingly used as the first-line imaging test in suspected PE and is available 24 hours a day at most institutions [10][11][12][13][14]. Pulmonary CTA not only allows direct visualization of emboli but provides information regarding the status of the right heart [15,16]. In several studies, the ratio of the RV to left ventricle (LV) diameters on pulmonary CTA has been proposed as a sign for RV dysfunction [17][18][19]. Other signs have been describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 41 publications
(118 reference statements)
3
89
0
4
Order By: Relevance
“…However, this study was focused on the incremental value of combined assessment rather than comparisons between CT signs. Moreover, 2 previous studies reported that the volumetric assessment of ventricles showed higher interobserver agreement 4 and seemed to be superior for the identification of high-risk patients with adverse clinical outcomes. 5 …”
Section: Discussionmentioning
confidence: 96%
“…However, this study was focused on the incremental value of combined assessment rather than comparisons between CT signs. Moreover, 2 previous studies reported that the volumetric assessment of ventricles showed higher interobserver agreement 4 and seemed to be superior for the identification of high-risk patients with adverse clinical outcomes. 5 …”
Section: Discussionmentioning
confidence: 96%
“…Non-ECG-gated volumetric analysis seems to be slightly superior to identify high-risk patients with adverse clinical outcome compared to RV/LV diameter ratio measurements (71,74). Furthermore, axial and four-chamber view measurements of RV/LV diameter ratio have shown considerable interobserver variability, while volumetric measurements have shown better reproducibility (71). In another study of 60 patients, a RV/LV volumetric ratio >1.28 measured in non-ECG-gated CTPA showed 89% sensitivity, 75% specificity, 42% PPV and 97% NPV to predict adverse clinical outcome (74).…”
Section: Rv Dysfunctionmentioning
confidence: 95%
“…A RV/LV diameter ratio cutoff value of >1.0 is commonly considered to represent RV dysfunction and has been shown to predict short-term adverse outcome and mortality (10,71,72). Axial and four-chamber view measurements of RV/LV diameter ratio >1.0 are comparable for predicting 30-day mortality (10,73).…”
Section: Rv Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations